2010
DOI: 10.1007/s10614-010-9233-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Economic and Activity and Stabilization Policies in the CIS

Abstract: Business cycles, Neural network, Out-of-sample forecasts, Recession, Real GDP,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…The authors showed (e.g. see Anderson and Vahid (1998) [1], Kiani (2011) [11], and Kiani and Bidarkota (2004) [12]) that most macroeconomic time series are nonlinear, and hence linear models should not be used for forecasting fluctuations in economic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed (e.g. see Anderson and Vahid (1998) [1], Kiani (2011) [11], and Kiani and Bidarkota (2004) [12]) that most macroeconomic time series are nonlinear, and hence linear models should not be used for forecasting fluctuations in economic activity.…”
Section: Introductionmentioning
confidence: 99%